Computational fluid dynamics simulation and performance optimization of an electrical vehicle Air-conditioning system - Tan, Libin; Yuan, Yuejin (Alexandria engineering journal, 2022)
In vehicles, air conditioning tends to offer efficient thermal conditioning and air circulation inside cabin for passenger comfort from different climate variation. The working performance of air conditioning system in vehicles is an essential factor for thermal comfort and driving safety of the passenger compartment of vehicles. Therefore, it is of great significance to construct a numerical simulation model for theoretical analysis and performance evaluation of vehicle air conditioning system. In current research, the air conditioning system of an electric vehicle is taken as the research subject. Internal flow field characteristics of air conditioning system is investigated by Computational Fluid Dynamics (CFD). Results show that the air flow in air-conditioning system is relatively smooth, and the velocity distribution in the front windshield A area and the driver's field of vision of the left and right windows is not ideal when the defrosting-demisting mode is on; the velocity and air quantity distribution of the two outlets in the middle air duct are not uniform under blowing mode. In view of the uneven distribution of velocity and air quantity, the corresponding optimization scheme is proposed. After optimization, the cell relative velocity of the front windshield is significantly improved, and velocity distribution of the side window glass is slightly increased and the defrosting-demisting performance meets the vehicle defrosting requirements of national standard; after optimization, the air quantity distribution of the air ducts at blowing mode is more uniform, which is conducive to the comfort of the passenger compartment.